Gastrodia protects HT22 cells from damage caused by oxygen glucose deprivation and reperfusion through inhibiting ferroptosis - Dongyue Zhou; Zhixuan Huang; Jian Liu; Jinlong Tan; Hui Li; Yangwen Ai (Scientific Reports)
Abstract Gastrodin (Gas) is a key active ingredients of Gastrodia elata Bl., with applications in treating cardiovascular and neurodegenerative conditions. However, the impact of Gas on neuronal damage caused by cerebral ischemia/reperfusion remains uncertain. A cell model of oxygen-glucose deprivation/reoxygenation (OGD/R) was established and the viability and apoptosis of HT22 cells were measured using the CCK-8 assay and TUNEL staining. Different kits detected the levels of LDH, Fe2+ and MDA. The levels of ferroptosis-related genes and proteins were evaluated utilizing RT-qPCR and Western blotting. Following OGD/R, there was a decrease in HT22 cell viability and an increase in LDH level and apoptosis rate. Gas (25µM) increased cell viability, decreased LDH, Fe2+, MDA and ACSL4 levels, up-regulated SLC7A11 and GPX4 and ameliorated OGD/R-induced apoptosis (P < 0.01). Ferroptosis inducer Erastin (Era, 10µM) successfully induced ferroptosis in HT22 cells, while Gas treatment attenuated the effect of Era. Era further promoted OGD/R-induced damage and ferroptosis in HT22 cells, whereas Gas inhibited the effect of Era. In conclusion, Gas might provide protection against induced HT22 cell injury caused by OGD/R through inhibiting ferroptosis, shows promising potential for clinical treatment of cerebral ischemia/reperfusion.